TikTok as a Media for Self-Existence among Gen Z in the Middle of the Covid-19 Pandemic - Aliah, Ai Rida Himatul; Nurfazri, Muhammad (Universitas Muhammadiyah Surakarta, 2023)
The use of new media during the Covid-19 pandemic is increasing among several generations, especially Gen Z, who are categorized as a generation that is very close to technology. They often use TikTok as primary media. TikTok is a platform that provides a lot of information in videos. This study aims to determine the self-concept of sociology students at UIN Sunan Gunung Djati Bandung in using TikTok, the factors driving the use of TikTok, and changes in attitudes that occur due to the use of TikTok. A descriptive qualitative is used to describe the use of TikTok in Sociology Students at UIN SGD Bandung. This research investigates various self-existences on TikTok in terms of self-perceptions, promoting beauty and fashion, education, relaxation, and attitudes. On the other hand, Mead's theory explains the desire to be equal to others. Also, Mead said that another self-concept is the existence of new sources of information and educational media during the Covid-19 outbreak. Thus, this research can provide an overview of the use of TikTok as a medium of self-existence that can benefit its users.